2018
DOI: 10.1080/15476286.2018.1526541
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of vertebrate Nocturnin: insights and remaining mysteries

Abstract: Post-transcriptional control of messenger RNA (mRNA) is an important layer of gene regulation that modulates mRNA decay, translation, and localization. Eukaryotic mRNA decay begins with the catalytic removal of the 3′ poly-adenosine tail by deadenylase enzymes. Multiple deadenylases have been identified in vertebrates and are known to have distinct biological roles; among these proteins is Nocturnin, which has been linked to circadian biology, adipogenesis, osteogenesis, and obesity. Multiple studies have inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…Mitochondrial targeting signals typically reside in the first 90 Nterminal residues, form amphipathic helices, have a high arginine content, and contain few negatively charged residues (27). Consistent with these features, amino acids 2-15 are predicted to be an amphipathic alpha-helix and the first 74 amino acids have an isoelectric point of 12.1, with 12 arginines and only one negatively charged residue (6). Deletion of amino acids 2-15 reduced the MitoFates probability score from 0.94 to 0.035.…”
Section: Nocturninmentioning
confidence: 95%
See 4 more Smart Citations
“…Mitochondrial targeting signals typically reside in the first 90 Nterminal residues, form amphipathic helices, have a high arginine content, and contain few negatively charged residues (27). Consistent with these features, amino acids 2-15 are predicted to be an amphipathic alpha-helix and the first 74 amino acids have an isoelectric point of 12.1, with 12 arginines and only one negatively charged residue (6). Deletion of amino acids 2-15 reduced the MitoFates probability score from 0.94 to 0.035.…”
Section: Nocturninmentioning
confidence: 95%
“…Previously, over-expressed, epitope tagged NOCT was reported to be either cytoplasmic or peri-nuclear, whereas endogenous NOCT has been reported to localize to the nucleus or cytoplasm of cells in mouse embryos or to the cytoplasm in Xenopus retina (2,9,22,23). Intriguingly, sequence analysis of the unique Nterminus of mouse and human NOCT detected the presence of a putative mitochondrial targeting sequence (Figure 1a) (6). Moreover, we observed that the N-terminus of NOCT possesses two potential translation initiation sites, one of which would include the mitochondrial targeting sequence and one which would exclude it.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations